2018
DOI: 10.18632/oncotarget.24652
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative parameters in dynamic contrast-enhanced magnetic resonance imaging for the detection and characterization of prostate cancer

Abstract: Objectivesto assess the diagnostic accuracy of quantitative parameters of DCE-MRI in multi-parametric MRI (mpMRI) in comparison to the histopathology (including Gleason grade) of prostate cancer.Patients and methods150 men with suspected prostate cancer (abnormal digital rectum examination and or elevated prostate-specific antigen) received pre-biopsy 3T mpMRI and were recruited into peer-reviewed, protocol-based prospective study. The DCE-MRI quantitative parameters (Ktrans (influx transfer constant) and kep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The GS for each patient was obtained. The radical prostate specimens for histology were sliced in patient-specific moulds to aid orientations between imaging and histology, which were fabricated using a 3D printer as described by our group and others previously 12,13 . Specifically, patient specific 3D printed moulds were made prior to surgery based on the T2-weighted MRI prostate capsule the moulds were customised for each patient using MIMICS and Solidworks.…”
Section: Methodsmentioning
confidence: 99%
“…The GS for each patient was obtained. The radical prostate specimens for histology were sliced in patient-specific moulds to aid orientations between imaging and histology, which were fabricated using a 3D printer as described by our group and others previously 12,13 . Specifically, patient specific 3D printed moulds were made prior to surgery based on the T2-weighted MRI prostate capsule the moulds were customised for each patient using MIMICS and Solidworks.…”
Section: Methodsmentioning
confidence: 99%
“…Previous published studies have reported USWE to have a high diagnostic accuracy in clinical staging and localization of tumors within prostate glands of men suspected of PCa (6, 7, 10, 11, 15, 16). Our findings in this study add to the existing knowledge and show that measurement of stiffness in kPa increase BCR prediction ability of clinicopathological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Then, radical prostatectomy was usually done within 2 months (62 days targets) after MRI in this cohort. MRI protocol was derived from the European Society of Uro-radiology Guidelines (ESUR) 2012 (13) for PCa detection; acquisition parameters are shown and summarized in Table 2 (10, 11). All MR images were analyzed and scored by experienced uro-radiologists (SA, SMB) using PI-RADS v2.0; patients' clinicopathology data were blinded to both radiologists.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations